Correction: Klain et al. The Prevention of House Dust Mite Allergies in Pediatric Asthma. Children 2024, 11, 469 - Angela Klain; Antonio Andrea Senatore; Amelia Licari; Francesca Galletta; Irene Bettini; Leonardo Tomei; Sara Manti; Francesca Mori; Michele Miraglia del Giudice; Cristiana Indolfi (MDPI AG, 2024)
There was an error in the original publication [...]